2003
DOI: 10.1038/sj.ejhg.5201035
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of the cystic fibrosis transmembrane conductance regulator (CFTR) gene, the cationic trypsinogen (PRSS1) gene, and the serine protease inhibitor, Kazal type 1 (SPINK1) gene in patients with alcoholic chronic pancreatitis

Abstract: Susceptibility to alcoholic chronic pancreatitis (ACP) could be genetically determined. Mutations in cationic trypsinogen (PRSS1), cystic fibrosis transmembrane conductance regulator (CFTR), and serine protease inhibitor, Kazal type 1 (SPINK1) genes have been variably associated with both the hereditary and the idiopathic form of chronic pancreatitis (CP). Our aim was to analyze the three genes in ACP patients. Mutational screening was performed in 45 unrelated ACP patients and 34 patients with alcoholic liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 33 publications
1
15
1
1
Order By: Relevance
“…Several large studies focused on the association of ICP, and the most common trypsinogen mutations (R122H and N29I) have shown a frequency of mutations ranging from 0.2 to 10% of patients [28][29][30][31][32] . PRSS1 mutations are rarely found in ACP patients [33][34][35] . O'Reilly et al [11] described the R122H muta- Age is expressed as median and range.…”
Section: Discussionmentioning
confidence: 99%
“…Several large studies focused on the association of ICP, and the most common trypsinogen mutations (R122H and N29I) have shown a frequency of mutations ranging from 0.2 to 10% of patients [28][29][30][31][32] . PRSS1 mutations are rarely found in ACP patients [33][34][35] . O'Reilly et al [11] described the R122H muta- Age is expressed as median and range.…”
Section: Discussionmentioning
confidence: 99%
“…However, the researches have not found any mutations of the PRSS1 gene in patients with alcoholic pancreatitis [8,14] . In Brazil, the E79K change in exon 3 was detected in 1 patient with alcohol-related chronic pancreatitis but with no difference when compared to control subjects [12] .…”
mentioning
confidence: 96%
“…This mutation's analysis has always been negative in ACP (13)(14)(15)(16), confirming that PRSS1 mutations play no role in pancreatic damage in patients who drink alcohol. A recent study also showed that PRSS1 mutations were not detected in Indian patients with hereditary and nonhereditary CP, including ACP (17).…”
Section: Spink1 Prss1 and Cftr Mutations In Acp Patientsmentioning
confidence: 68%
“…Sharer et al looked for 22 different mutations; in patients with ACP, the CFTR mutation rate was 8.5%; significantly higher than the control group (26). However, subsequent studies failed to establish any significant difference between ACP patients, the healthy population and the control groups (13,14,25,27). Two studies from Brazil showed that different methods could affect the results of the study.…”
Section: Spink1 Prss1 and Cftr Mutations In Acp Patientsmentioning
confidence: 99%